Practical approaches for overcoming challenges in heightened characterization of antibody-drug conjugates with new methodologies and ultrahigh-resolution mass spectrometry. Issue 3 (3rd April 2018) - Friese, Olga V.; Smith, Jacquelynn N.; Brown, Paul W.; Rouse, Jason C.
ABSTRACT: Antibody-drug conjugation strategies are continuously evolving as researchers work to improve the safety and efficacy of the molecules. However, as a part of process and product development, confirmation of the resulting innovative structures requires new, specialized mass spectrometry (MS) approaches and methods, as compared to those already established for antibody-drug conjugates (ADCs) and the heightened characterization practices used for monoclonal antibodies (mAbs), in order to accurately elucidate the resulting conjugate forms, which can sometimes have labile chemical bonds and more extreme chemical properties like hydrophobic patches. Here, we discuss practical approaches for characterization of ADCs using new methodologies and ultrahigh-resolution MS, and provide specific examples of these approaches. Denaturing conditions of typical liquid chromatography (LC)/MS analyses impede the successful detection of intact, 4-chain ADCs generated via cysteine site-directed chemistry approaches where hinge region disulfide bonds are partially reduced. However, this class of ADCs is detected intact reliably under non-denaturing size-exclusion chromatography/MS conditions, also referred to as native MS. For ADCs with acid labile linkers such as one used for conjugation of calicheamicin, careful selection of mobile phase composition is critical to the retention of intact linker-payload during LC/MS analysis. Increasing the pH of the mobile phase prevented cleavage of a labile bond in the linker moiety, and resulted in retention of the intact linker-payload. In-source fragmentation also was observed with typical electrospray ionization (ESI) source parameters during intact ADC mass analysis for a particular surface-accessible linker-payload moiety conjugated to the heavy chain C-terminal tag, LLQGA (via transglutaminase chemistry). Optimization of additional ESI source parameters such as cone voltages, gas pressures and ion transfer parameters led to minimal fragmentation and optimal sensitivity. Ultrahigh-resolution (UHR) MS, combined with reversed phase-ultrahigh performance (RP-UHP)LC and use of the FabRICATOR® enzyme, provides a highly resolving, antibody subunit-domain mapping method that allows rapid confirmation of integrity and the extent of conjugation. For some ADCs, the hydrophobic nature of the linker-payload hinders chromatographic separation of the modified subunit/domains or causes very late elution/poor recovery. As an alternative to the traditionally used C4 UHPLC column chemistry, a diphenyl column resulted in the complete recovery of modified subunit/domains. For ADCs based on maleimide chemistry, control of pH during proteolytic digestion is critical to minimize ring-opening. The optimum pH to balance digestion efficiency and one that does not cause ring opening needed to be established for successful peptide mapping.